Meningkatkan Aktivitas Dan Hasil Belajar Matematika Menggunakan Kombinasi Model PBL, SR, Dan CRH Di SDN Antasan Kecil Timur 3 Banjarmasin - Rini Wahyuni; Ahmad Muhyani Rizalie (Inspirasi Dunia: Jurnal Riset Pendidikan dan Bahasa, 2023)
The problem raised in this study is the low activity and student learning outcomes. Effort to overcome this problem is to apply learning with a combination of Problem Based Learning, Simultaneous Roundtable, and Course Review Horay models. The aim of the research is to describe teacher activities, analyze student activities, and student learning outcomes. The study used classroom action research which was carried out in 4 meetings. The subjects of this research were fourth grade students at SDN Antasan Kecil Timur 3 Banjarmasin, with 24 students consisting of 12 male students and 12 female students in the 2022/2023 school year. This research uses a qualitative approach. The results showed that teacher activitie scored 97 in the very good category. Student activities get a score 96 with very active category. Cognitive learning outcomes achieve 96% completeness and affective and psychomotor learning outcomes achieve 100% completeness.